Harnessing AEM electrolyzer-level performance through strategically designing the electronic structure of electrocatalysts, enabling dynamic functional switching - Kumar, Sonu; Verma, Tushar Singh; Selvaraj, Kaliaperumal (ACS Catalysis, 2025)
The anion exchange membrane water electrolyzer (AEMWE) is a promising technology for cost-effective hydrogen production. To promote its development and adoption, targeted efforts are focused on finding non-platinum group metal (non-PGM) electrocatalysts that efficiently facilitate the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Nickel sulfides (NiS) are effective OER catalysts; however, they suffer due to leaching-related instability at electrolyzer stack operational conditions. We introduce a rational non-PGM design that enhances stability during the OER while excelling at the HER, showcasing molecular-level insights for a scalable AEMWE zero-gap stack device. NiS coating is applied to the Al-metal-organic framework supported by 3D porous nickel foam (NSMA), leading to charge localization at the interface, which helps in OER by requiring only 322 millivolts at 100 mA cm-2. The main innovation in the NSMA design is a controlled electroreduction process that converts the Millerite phase into Ni3S2, a catalyst (rNSMA). This transformation leads to charge delocalization at the surface and a low overpotential of -80 mV at -100 mA cm-2 for the HER. In a full cell, this catalyst duo requires an overpotential of 1.49 V, outperforming the commercial Pt/Ru catalyst pair at 1.58 V. In a scaled-up 12.96 cm2 AEM electrolyzer single-cell stack, current density rose from 398 to 1062 mA/cm2, maintained for over 100 h at high temperatures, achieving 99% Faradaic efficiency and 100% hydrogen purity. The AEM electrolyzer cell shows a good energy efficiency of 45.50 kWh/kg and a cell efficiency of 86.59%. Detailed studies, including DFT analyses, revealed that electronic structure modification enhances charge delocalization, driving its impressive performance on an industrially significant scale.
Keywords: anion exchangemembrane water electrolyzer (AEMWE); charge transfer; density functional theory(DFT); HER; nickel sulfide; OER